Modeling and optimization of processing parameters of strips produced from blends of cassava and cowpea flour - Adeyanju, James Abiodun; Abioye, Adekanmi Olusegun; Ogunlakin, Grace Oluwatoyin; James, Oyelade Olusegun; Adesina, Deborah Adeola; Oloyede, Abiola Adewale (My University, 2022)
Most Nigerian traditional foods have a low nutritional value, inconsistent sensory attributes, and short shelf life. Thus, upgrading becomes necessary for the technologies used in the processing, distributing, and storing of indigenous snack foods to improve the products' nutritional, sensory, and storage properties. A Box-Behnken (three-factor) response surface methodology was used to optimize the process. The effect of frying temperature (160 - 180°C), frying time (8 - 12 min) and percent cowpea flour (10 - 30%) on some attributes (moisture, fat, protein contents, texture, and color change) of cassava-cowpea strips fried snack. Data were analyzed by ANOVA and regression analysis. The moisture content ranged between 1.00% and 4.26%, fat content (8.41–11.94%), protein content (30.83–36.42%), texture (5.06–13.14 N) and color change (26.967–40.479). Frying temperature, frying time and % cowpea flour had a significant (P < 0.05) effect on moisture, fat, protein contents, texture and color change of cassava-cowpea strips. The processing conditions affected moisture, fat, protein, texture, and color change. Coefficients of determination, R2 were 0.87, 0.86, 0.79, 0.88 and 0.71, respectively. The best conditions for processing cassava-cowpea strips were 12 min frying time, 166.65 °C frying temperature, and 24.36% cowpea flour content. The desirability of optimization was 0.65. Therefore, composite flour from cassava and cowpea can be adopted or used to produce strips to prevent protein-energy malnutrition in the community
Article
Keywords: Box-Behnken Design; Frying Temperature; Frying Time; Optimization; Quality Attributes